2017
DOI: 10.2147/ijn.s133833
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional collagen-graphene as colloidal templates for biocompatible inorganic nanomaterial synthesis

Abstract: In this study, natural graphite was first converted to collagen-graphene composites and then used as templates for the synthesis of nanoparticles of silver, iron oxide, and hydroxyapatite. X-ray diffraction did not show any diffraction peaks of graphene in the composites after inorganic nucleation, compared to the naked composite which showed (002) and (004) peaks. Scanning electron micrographs showed lateral gluing/docking of these composites, possibly driven by an electrostatic attraction between the positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The rst peak at 2Q ¼ 19.6 was related to the homogenous mixing of PVA and alginate within the bers and the second was graphene nanosheet's characteristic peak according to other researches. 49,50 According to XRD patterns of pure PVA and alginate, both were semicrystalline with a broad peak at 2Q ¼ 19.3 and 26.6 , respectively. Aer mixing, both peaks disappeared and only one peak at 2Q ¼ 19.6 could be detected which could be due to their homogeneous blending and the interactions between them.…”
Section: Fabrication and Characterization Of The Gr-ap Scaffoldsmentioning
confidence: 99%
“…The rst peak at 2Q ¼ 19.6 was related to the homogenous mixing of PVA and alginate within the bers and the second was graphene nanosheet's characteristic peak according to other researches. 49,50 According to XRD patterns of pure PVA and alginate, both were semicrystalline with a broad peak at 2Q ¼ 19.3 and 26.6 , respectively. Aer mixing, both peaks disappeared and only one peak at 2Q ¼ 19.6 could be detected which could be due to their homogeneous blending and the interactions between them.…”
Section: Fabrication and Characterization Of The Gr-ap Scaffoldsmentioning
confidence: 99%
“…The X-ray diffraction (XRD) peaks of collagen-coated GF confirmed that they existed in separate planes. In addition, they did not interact with each other which is supported by their distinct peak positions without any considerable change that is supported by the above references [ 33 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 52%
“…After coating the GF with collagen, D peak appeared near 1350 cm −1 and some other peaks emerged including a minor peak at ~2450 cm −1 ( G ′ band). The defect was increased from 0.02 to 0.7 in collagen-coated GF which is estimated from the intensity ratio of the D band and G band ( D / G ) [ 33 ]. The amide-III peak appeared at 1242 cm −1 which is a characteristic of the collagen ( Figure 3(c) ), though the amide-I and amide-II peaks were absent in the spectra [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen–graphene–HA is another candidate for bone repair and regeneration, and drug delivery. The addition of graphene to the scaffold provided it with the capacity to synthesize and fold at the nanometric level [ 85 ]. Both graphene and its derivatives have denoted positive outcomes in nanomedicine approaches in bone repair, due to their additional mechanical properties and electrical conductivity, besides atomic structure stability.…”
Section: Most Relevant Polymeric Composites In Bone Regenerationmentioning
confidence: 99%